Response to the COVID-19 pandemic: Physics teaching in India - Madhurima, V.; Ramaswamy, Ram; Chari, Deepa; Nanal, Vandana; Saha-Dasgupta, Tanushri (AIP conference proceedings, 2023)
When academic institutions in India closed abruptly in March 2020 due to the COVID-19 pandemic, formal education moved online. This transition had a very uneven impact given the significant digital divide between rural and urban India and the unequal distribution of digital resources in different institutions. Access to resources varied substantially by individual, based on socioeconomic factors as well as gender. Institutional support to the academic community during this critical period was largely inadequate, which has had serious consequences on the teaching of physics and other subjects that require laboratory instruction. Educational institutions also provide safe and enabling learning spaces for women students; reduced access to such facilities undermined the work-and study-related dynamics for women because of the scarcity of resources such as devices, data and time. This paper reports on efforts made towards understanding such challenges during the COVID-19 pandemic, and describes steps that were taken to address them.